FAIL-T (AFP, AST, tumor sIze, ALT, and Tumor number): a model to predict intermediate-stage HCC patients who are not good candidates for TACE - Kaewdech, Apichat; Sripongpun, Pimsiri; Assawasuwannakit, Suraphon; Wetwittayakhlang, Panu; Jandee, Sawangpong; Chamroonkul, Naichaya; Piratvisuth, Teerha (Frontiers in Medicine, 2023)
Background Patients with unresectable hepatocellular carcinoma (HCC) treated with transarterial chemoembolization (TACE) are a diverse group with varying overall survival (OS). Despite several scoring systems predicting OS are available, one of the unsolved problems is which patients might not benefit from TACE. We aim to develop and validate a model to identify HCC patients who would survive < 6 months after their 1st TACE. Methods Patients with unresectable HCC, BCLC stage 0-B, who underwent TACE as their 1st and sole treatment between 2007 and 2020 were included. Demographic, laboratory data, and tumor characteristics before the 1st TACE were obtained. Eligible patients were randomly allocated in a 2:1 ratio into training and validation sets. The former was used for model development using stepwise multivariate logistic regression, then the model was validated in the latter set. Results A total of 317 patients were included (210 for training set, and 107 for validation set). Baseline characteristics of the two sets were comparable. The final model (FAIL-T) comprised AFP, AST, tumor sIze, ALT, and Tumor number. The FAIL-T model yielded AUROCs of 0.855 and 0.806 for predicting 6-month mortality after TACE in the training and validation sets, respectively. While “six-and-twelve” score showed AUROCs of 0.751 (P<0.001) in the training and 0.729 (P=0.099) in the validation sets for the same purpose. Conclusions FAIL-T is useful for predicting 6-month mortality among naïve HCC patients undergoing TACE. HCC patients with high FAIL-T scores may not benefit from TACE; and other treatment options, if available, should be considered.